Dialect and region: The complex linguistic system of Malaysian Chinese prose - Shy, F.P.; Kheng, Y.K.; Soon, L.T. (2011)
Malaysia has the largest Chinese population apart from Mainland China, Taiwan, Hong Kong and Macao. Literature in the Chinese language has taken root and developed in this area since 1919. As Malaysia is situated at the cross-roads of Eastern and Western civilizations, the mixture of cultures and languages produced a Malaysian Chinese literature, quite different from the literature of China. Its most prominent distinction lies in the use of-language. The authors resort to vocabulary from local dialects and languages and specific foreign loanwords, achieving a strong local color of ``Southern seas''. The paper takes The Reader of Malaysian Chinese Prose as linguistic material to discuss ``malaysianized'' vocabulary, the influence of local culture on literary language and the deep cultural background of Malaysian Chinese literature.